DESAIN LANSKAP WISATA BERBASIS MASYARAKAT SEBAGAI UPAYA PEMULIHAN LAHAN BEKAS TAMBANG GALIAN C DI KABUPATEN PADANG PARIAMAN - Radnawati, Daisy; Makhmud, Desy Fatmala (Jurnal Lingkungan dan Kota, 2024)
One of the Open Access Land (OAL) locations is in Lubuk Alung Village, Padang Pariaman Regency, West Sumatra, which is an ex-mining C-excavation area of ​​7 hectares. The current condition of the site is in the form of waterlogged holes, open areas with no topsoil layer, grooves water, and vegetated soil. Environmental conservation efforts based on community participation are needed in an effort to improve the quality of the environment and for the local community. This study was conducted in September-November 2020 using a qualitative descriptive analysis method, data on the situation and field conditions were obtained from direct observations and interviews, the analysis process used a design approach. The restoration of OAL in this location has the potential to be used as a water recreation area, besides that, tourism supporting facilities and infrastructure are also needed that can help the economy of the surrounding community. Nature-based planning is carried out by optimizing the flora and fauna typical of wetlands. The potential of the site to be used as an area for fish cultivation and agriculture can be applied. The tourism concept is divided into fish farming tourism, agriculture, culinary, handicrafts typical of West Sumatra and wetland areas as outbound tourism, the concept of planning for the rehabilitation of OAL Lubuk Alung is then outlined in the visual design of community-based tourism landscapes.